Genomic and clinical characterization of Klebsiella pneumoniae carrying the pks island - Wang, Zhiqian; Liu, Yanjun; Liu, Peilin; Jian, Zijuan; Yan, Qun; Tang, Bin; Yang, Awen; Liu, Wenen (Frontiers in Microbiology, 2023)
The pks island and its production of the bacterial secondary metabolite genotoxin, colibactin, have attracted increasing attention. However, genomic articles focusing on pks islands in Klebsiella pneumoniae, as well as comparative genomic studies of mobile genetic elements, such as prophages, plasmids, and insertion sequences, are lacking. In this study, a large-scale analysis was conducted to understand the prevalence and evolution of pks islands, differences in mobile genetic elements between pks-negative and pks-positive K. pneumoniae, and clinical characteristics of infection caused by pks-positive K. pneumoniae. Methods: The genomes of 2709 K. pneumoniae were downloaded from public databases, among which, 1422 were from NCBI and 1287 were from the China National GeneBank DataBase (CNGBdb). Screening for virulence and resistance genes, phylogenetic tree construction, and pan-genome analysis were performed. Differences in mobile genetic elements between pks-positive and pks-negative strains were compared. The clinical characteristics of 157 pks-positive and 157 pks-negative K. pneumoniae infected patients were investigated. Results: Of 2709 K. pneumoniae genomes, 245 pks-positive genomes were screened. The four siderophores, type VI secretion system, and nutritional factor genes were present in at least 77.9% (191/245), 66.9% (164/245), and 63.3% (155/245) of pks-positive strains, respectively. The number and fragment length of prophage were lower in pks-positive strains than in pks-negative strains (P < 0.05). The prevalence of the IS6 family was higher in pks-negative strains than in pks-positive strains, and the prevalence of multiple plasmid replicon types differed between the pks-positive and pksnegative strains (P < 0.05). The detection rate of pks-positive K. pneumoniae in abscess samples was higher than that of pks-negative K. pneumoniae (P < 0.05). Conclusions: The pks-positive strains had abundant virulence genes. There were differences in the distribution of mobile genetic elements between pks-positive and pks-negative isolates. Further analysis of the evolutionary pattern of pks island and epidemiological surveillance in different populations are needed.